Tumores de glándulas salivales: enfrentamiento diagnóstico inicial - González A, Tomás; Fuenzalida M, Lucas; Gac E, Patricio; Rodríguez M, Francisco; Cabané T, Patricio; Rappoport W, Daniel (Revista Hospital Clínico Universidad de Chile, 2021)
It is described that salivary gland tumors account for up to 3-6% of head and neck tumors, 80% of these being located in the parotid gland. Broadly speaking, the smaller the gland, the greater the probability of malignancy. The most common clinical manifestation in tumor pathology is the appearance of a painless mass. Indicators of malignancy should be considered: chronic volume increase or rapid growth, facial paralysis, cranial nerve involvement, ulceration, and cervical lymphadenopathy. Ultrasonography should be the first imaging study, however, it provides limited information. MRI is the exam of choice for salivary gland tumors, whereas CT and PET-CT allow the study of local and remote invasion. FNA is controversial, it is not indicated for all patients, in parotid tumors a cytological examination is usually not necessary prior to surgery. Excisional biopsy is not recommended due to the risk of tumor seeding, neural damage, and salivary fistula. The goal of treatment in gland tumors is the removal of the glands, associated with lymph node dissection and adjuvant radiation therapy in indicated cases. The general practitioner must comprehensively address these pathologies to achieve a timely referral to the specialist.